The Important Benefits of Marriage Itsbat from The Compilation of Islamic Law Perspective - Mardalena Hanifah; Meidana Pascadinianti; Maulidya Triyananda (International Conference On Law And Social Sciences, 2024)
A marriage itsbat is an application to legalize a marriage before the Religious Court for Muslim people. If you cannot prove the marriage occurred with a marriage certificate, then you can apply for a marriage itsbat to the Religious Court. In this case, the application for a marriage itsbat is submitted to the Religious Court if the marriage has fulfilled the provisions of the Islamic religion and does not conflict with the pillars and conditions of marriage. According to Article 7 of Presidential Instruction No. 1 of 1991 on the Compilation of Islamic Law, marriage can only be verified by a marriage certificate issued by a marriage registrar. The study method employed is normative juridical, which includes research on legal principles, which are fundamental concepts in law that can be used to guide decisions. The research conducted was descriptive, meaning it was described and explained in clear and thorough language. The analysis is qualitative. A qualitative analysis is a study that examines the integration of the substance of legislative rules. According to research findings, marriage applications itsbat are made to obtain their child's birth certificate, register for school, and register for civil service tests, or TNI/POLRI. Given this reality, they obtain a marriage certificate by referring to their marriage; also, it provides legal protection for their children born from the marriage, as children are not at fault and their status must be preserved. Marriage itsbat seeks to ensure that the marriage is conducted with valid evidence in the form of a marriage certificate extract and that it is legalized both legally, formally, and throughout the community.